IMPLICATIONS USING ELECTRONIC STAMP DUTY AUTHENTIC AS PROOF OF ELECTRONIC DOCUMENTS IN INDONESIA - Febia Salwa Pandora; Edmon Makarim (Universitas Lampung, 2022)
The rapid development of the times affects all aspects of life. In this digital era, government regulations must also follow the flow of changes, including stamp duty. In 2020, the Minister of Finance, Sri Mulyani, inaugurated the e-Material. This electronic stamp duty issuance raises questions about its implications for its use as proof of document authenticity. This study aims to explain the use of e-stamp as a means of proving their authenticity and provide answers to their benefits to the community. This research uses a normative method through searching regulations and applicable regulations and synchronizing existing research data with applicable laws. The implementation of the stamp duty system is still preserved in Indonesia even though the Netherlands itself, as the originator, has not implemented the system for a long time. Trough stamp duty has a budgetary function and a document authentication function, there are still many shortcomings in the authentication function. The absence of recording information regarding the purchaser of stamp duty, identity, and description of what documents are attached creates ineffectiveness on the authenticity proof function. In contrast, the later proves that system in Indonesia is still not qualified, and it is sufficient to say that the sealing system must apply the rules of information security law.